KONDISI VEGETASI PADA LOKASI LIMA DAN SATU TAHUN SETELAH TEBANGAN DI WILAYAH IUPHHK PT. AYA YAYANG INDONESIA, KABUPATEN TABALONG - Didi Julkurnain; Suyanto Suyanto; Setia Budi Peran (Jurnal Sylva Scienteae, 2020)
PT. Aya Yayang Indonesia is a company engaged in forestry by utilizing wood as a result of its production, with the existence of this company's activities will certainly infact to the biodiversity of vegetationthat exist in the area. The objectives of this study were to analyze vegetation conditions in the area of five year after logging (RKT 2012) and one year after logging (RKT 2016) by analyse the Importance Value Index (IVI), diversity index, evenness index, dominance index and simmilirity index. This research is expected to provide information to related parties about the condition of vegetation in the area. The results obtained that IVI includes excellent criteria at a growth stageof seedlings and sapling have IVI> 160% and pole and tree growth stage have IVI> 240%. Species diversity in this area is moderate because each growth stage in both sites gets results with values> 2 and <3. The level of evenness of each growth stage in both locations has a value of> 0.6 so as to enter the high criterion. The highest dominant index is at every growth stage in RKT 2012 indicating that in this area there are species that dominate other species, and these two locations have similar similarity indexes on growth stage of seedlings, sapling, and trees with values > 50%, but at a growth stage that does not resemble a value < 50%, and at the level of trees that have similar similarity obtained value of 74.9% is close to 100%.Keywords: logging over forest; important value index; diversity index; evenness index; dominance index; simmilirity index